Analysis of socio-economic indicators in the context of the regional development of Eastern Croatia - Lončar, Jelena; Marinković, Veni (Hungarian Geographical Bulletin, 2015)
The main goal of this paper is to analyse socio-demographic processes in Eastern Croatia. We focus especially on the structure of particular economic activities as well as population, which should be the basis of regional development. We have used several demographic and economic indicators to determine the changes that have taken place in the region. Trends in population change in the last decades, the share of industrial and agricultural workers in legal entities, the share of employed and unemployed persons in cities and municipalities, as well as the inactive population in five Eastern Croatian counties are examined. Also, agricultural indicators have been analysed, as this is one of the most important economic activities in this area. Thereby, an overview of the main trends in regional development of this area has been given, although some of the data were unavailable at the local level. Altogether, the authors have analysed 126 local units (22 cities and 104 municipalities) within five counties of the Eastern Croatian region.